Parametric sensitivity and control of on-orbit manipulators during impacts using the Centre of Percussion concept. (February 2016) - Paraskevas, Iosif S.; Papadopoulos, Evangelos G.
Abstract: During capture of a free-flying object, a robotic servicer can be subject to impacts, which may separate it from the object or damage crucial subsystems. However, the reactions can be minimized using the Centre of Percussion (CoP) concept. Following a brief introduction of the two- and three-dimensional cases, the performance of a robot under impact is assessed when the CoP concept is employed. The effects of the parametric uncertainties on manipulator joint reactions are studied. Α control method to compensate for the reaction forces is proposed. Implementation guidelines are discussed. Simulations of a planar space robot validate the analysis.